Osmolyte-induced conformational changes in the Hsp90 molecular chaperone - Street, Timothy O (Wiley Subscription Services, Inc., A Wiley Company, 2010)
Osmolytes are small molecules that play a central role in cellular homeostasis and the stress response by maintaining protein thermodynamic stability at controlled levels. The underlying physical chemistry that describes how different osmolytes impact folding free energy is well understood, however little is known about their influence on other crucial aspects of protein behavior, such as native-state conformational changes. Here we investigate this issue with the Hsp90 molecular chaperone, a large dimeric protein that populates a complex conformational equilibrium. Using small angle X-ray scattering we observe dramatic osmolyte-dependent structural changes within the native ensemble. The degree to which different osmolytes affect the Hsp90 conformation strongly correlates with thermodynamic metrics of their influence on stability. This observation suggests that the well-established osmolyte principles that govern stability also apply to large-scale conformational changes, a proposition that is corroborated by structure-based fitting of the scattering data, surface area comparisons and m-value analysis. This approach shows how osmolytes affect a highly cooperative open/closed structural transition between two conformations that differ by a domain-domain interaction. Hsp90 adopts an additional ligand-specific conformation in the presence of ATP and we find that osmolytes do not significantly affect this conformational change. Together, these results extend the scope of osmolytes by suggesting that they can maintain protein conformational heterogeneity at controlled levels using similar underlying principles that allow them to maintain protein stability; however the relative impact of osmolytes on different structural states can vary significantly.